ANALISIS DAYA SAING DALAM STRATEGI PENGEMBANGAN KOMPETENSI DAERAH : STUDI KASUS DI KABUPATEN MEMPAWAH KALIMANTAN BARAT - ARIFIN, ARIFIN (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
Mempawah Regency is one of the districts that can be supported by the various sectors of the economy. Mapping the competitiveness of the regional economic sector in Mempawah Regency is one of the crucial issues. The research results show that the agricultural sectors are one of the mainstay sectors of Mempawah Regency. The others that are quite potential are the plantation, forestry and fisheries sectors. The developing sectors are supported by aspects of natural resources that well managed. Other sectors have not been managed optimally or have even been neglect. Apart from the agricultural sector (agriculture, forestry, plantation and fisheries), other economic aspects have experienced significant development, namely the trade sector, the manufacturing sector, and the provision of accommodation, food and beverage, and other service sectors. This sector makes a unique contribution, namely in certain months which can provide a high enough contribution. Apart from the above-mentioned sectors, the sectors that need to be considered for their contribution to Regional Original Income (PAD) are the sectors of electricity and gas procurement, water supply, waste and waste processing, transportation and warehousing. Even though the agriculture, forestry and fisheries sectors and the manufacturing industry are superior/main sectors, new policies are needed as breakthroughs as an effort to maintain and increase the products of other superior new sectors. How do government efforts with policies are made so that the non-base sectors can become a base sector with a higher competitive level?